(untitled) (Western European Journal of Medicine and Medical Science, 2025)
This article examines the characteristics of pain syndrome in various phenotypes of endometriosis, focusing on its correlation with the localization and degree of lesions. The study aims to identify the relationship between the type of endometriotic lesion and the severity of pain experienced by patients. It highlights that pain intensity and its clinical manifestations depend not only on the anatomical location of the lesions but also on their histological depth and the presence of inflammatory reactions. Understanding these patterns is essential for improving diagnostic accuracy and selecting optimal therapeutic strategies for endometriosis management.